2021
DOI: 10.1088/1873-7005/abf3b4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lubrication in the non-Reynolds regime due to the non-negligible gap on the fluid permeation through a membrane

Abstract: To understand lubrication-induced membrane permeation, the effects of permeability and membrane geometry on lubrication pressure and permeate flux are studied in a range of a wall-membrane gap width wherein the effect of lubrication cannot be resolved using the Reynolds lubrication equation. The unresolvable lubrication effect (referred to as the non-Reynolds lubrication effect) is modelled by including a higher-order effect as the wall-tangential variation of the local Couette–Poiseuille velocity. Analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…3c,d,5c,d), stronger y-dependent trend is observed in the pressure field; in particular, high-and low-pressure regions near the flat plates are highlighted at t∕(H 0 ∕U 0 ) = 15.0 . The result indicates the presence of a regime that is not described by Reynolds lubrication equation, which is referred to as the non-Reynolds lubrication regime (Takeuchi et al 2021;Takeuchi and Gu 2019), hereafter.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3c,d,5c,d), stronger y-dependent trend is observed in the pressure field; in particular, high-and low-pressure regions near the flat plates are highlighted at t∕(H 0 ∕U 0 ) = 15.0 . The result indicates the presence of a regime that is not described by Reynolds lubrication equation, which is referred to as the non-Reynolds lubrication regime (Takeuchi et al 2021;Takeuchi and Gu 2019), hereafter.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…the distance between the lowest/highest point of the circular membrane and the bottom/top wall) having a value of (H 0 − D p )∕2 = 0.25D p , 0.50D p , 1.0D p , respectively. Although the case of the smallest gap is already out of the range of the ideal lubrication condition ≪ 1 , our previous studies (Takeuchi and Gu 2019;Takeuchi et al 2021) showed that the lubrication phenomenon can still be described by including a higher-order correction for a non-negligible gap. Note that the effective longitudinal length scales of the lubrication region can be estimated to (Takeuchi et al 2021), and the effective scales for the above three cases are 0.5D p , 0.71D p , and 1.0D p , respectively, which are sufficiently smaller than the domain length l, indicating that the permeation induced by lubrication pressure is influenced little by the mirror images of the circular membranes due to the periodic boundary condition.…”
Section: Lubrication-induced Mass Transport Through Circular Membranementioning
confidence: 96%
See 3 more Smart Citations